Analisa Problematika dan Solusi dalam Upaya Peningkatan Literasi Siswa di SMP Muhammadiyah 4 Prambon - Sumargo, Nova Aditya Suluh; Hima, Lina Rihatul (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to analyze problems and solutions in the literacy improvement program carried out at SMP Muhammadiyah 4 Prambon. The method used in this study is to use qualitative descriptive research by collecting data by interviewing responding teachers at the school and also the principal as the person in charge of the program that will be implemented to improve literacy at SMP Muhammadiyah 4 Prambon, namely the literacy program 10 minutes before learning activities begin and love the library which is carried out with a predetermined schedule at In its implementation, supervision and evaluation are always carried out by the principal as the person in charge of the activity, there are several problems that exist from students and also from the infrastructure of books.